2021
DOI: 10.1097/j.pain.0000000000002215
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in neuroimmune and glial mechanisms of pain

Abstract: Pain is the primary motivation for seeking medical care. Although pain may subside as inflammation resolves or an injury heals, it is increasingly evident that persistency of the pain state can occur with significant regularity. Chronic pain requires aggressive management to minimize its physiological consequences and diminish its impact on quality of life. Although opioids commonly are prescribed for intractable pain, concerns regarding reduced efficacy, as well as risks of tolerance and dependence, misuse, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 248 publications
4
46
0
2
Order By: Relevance
“…Studies in rodents have reported either sex difference or no sex difference in pain behaviors and analgesia, a part of which may be strain-dependent (Mogil, 2020 ). The mechanisms leading to sex difference in neuropathic pain encompass differential nociceptive neuron transcriptome (Mecklenburg et al, 2020 ), translatome (Tavares-Ferreira et al, 2020 ), and preferential involvement of macrophages/microglia in males and T lymphocytes in females, although not all studies concur to this conclusion (see Price and Ray, 2019 ; Mogil, 2020 ; Gregus et al, 2021 for recent reviews). Neutrophils have also been reported to account for sex differences in pain and opioid-mediated analgesia (Scheff et al, 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rodents have reported either sex difference or no sex difference in pain behaviors and analgesia, a part of which may be strain-dependent (Mogil, 2020 ). The mechanisms leading to sex difference in neuropathic pain encompass differential nociceptive neuron transcriptome (Mecklenburg et al, 2020 ), translatome (Tavares-Ferreira et al, 2020 ), and preferential involvement of macrophages/microglia in males and T lymphocytes in females, although not all studies concur to this conclusion (see Price and Ray, 2019 ; Mogil, 2020 ; Gregus et al, 2021 for recent reviews). Neutrophils have also been reported to account for sex differences in pain and opioid-mediated analgesia (Scheff et al, 2018 , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As sex differences were found here for DOR-mediated chronic pain processing, the above questions are expected to be explored by considering both sexes. More broadly, the role of astrocytic-DOR in CNS inflammation in chronic pain condition (Giovannoni and Quintana, 2020 ), in astrocytes-neurons and astrocytes-microglia interactions (Greenhalgh et al, 2020 ; Vainchtein and Molofsky, 2020 ), and in astrocytes communication with immune cells from the periphery (Gregus et al, 2021 ) could allow to better understand the relationships between astrocytes and other cells involved in opioid effects and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is lack of consensus in the literature regarding male and female specific pain pathways, sex dimorphism has been reported in the development and maintenance of neuropathic pain. 38 This includes sex differences in immune-mediated pain and the effect of sex hormones on nociception and morphine tolerance. 38 In our study men reported higher levels of pain interference with mood in univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“… 38 This includes sex differences in immune-mediated pain and the effect of sex hormones on nociception and morphine tolerance. 38 In our study men reported higher levels of pain interference with mood in univariate analyses. However, sex was no longer significantly associated with pain interference with mood in multi-variable models.…”
Section: Discussionmentioning
confidence: 99%